Enhancing From Healthy Eating to Green Energy: A Dual Approach to Student Education on Nutrition and Biodiesel (Renewable Energy) - Suardi, Suardi; Pawara, Muhammad Uswah; Alamsyah, Alamsyah; Nurcholik, Samsu Dlukha; Wulandari, Amalia Ika; Anggela, Anggela (Naval Architecture Department, Kalimantan Institut of Technology, 2025)
Adolescence represents a critical stage of physical and cognitive development, requiring balanced nutrition to support growth, concentration, and academic performance. However, many students still lack awareness of healthy dietary practices and continue to consume nutrient-poor foods, leading to increased risks of metabolic and cognitive disorders. To address this issue, a dual-focus educational program was implemented at SMA Negeri 6 Penajam Paser Utara, combining balanced nutrition education with the introduction of simple renewable energy technology through biodiesel production from waste cooking oil. The program, conducted in collaboration with the Kalimantan Institute of Technology (ITK), employed interactive lectures, demonstrations, and hands-on sessions to enhance student understanding. A pre-test and post-test evaluation involving 40 students demonstrated a substantial improvement in knowledge, increasing from 45% to 96% after the intervention. Participants also expressed strong positive responses to the integration of nutritional awareness and eco-friendly technology, recognizing its relevance to daily life and environmental sustainability. The results show that this dual educational approach effectively strengthens students’ understanding of healthy eating habits while promoting environmental responsibility through waste-to-energy concepts. Overall, the program highlights the potential of combining nutrition education and renewable energy literacy as a strategic model for school-based community outreach aimed at fostering healthier, more environmentally conscious future generations.